AGE OF THE KURIL DEEP-SEA BASIN (SEA OF OKHOTSK) - Bezverkhny V.L.; Gorovaya M.T.; Markevich V.S.; Pletnev S.P.; Nabiullin A.A. (My University, 2003)
Determination of the age of the Kuril deep-sea basin, one of the key structures of the Sea of Okhotsk region, is very important for solving the problem of its origin and structural evolution. In this connection, we studied the upthrusted part of the northern slope of the basin in the Terpeniya Swell area. Based on the geological-geophysical data on the seafloor and island, it is established that a horst related to a system of upthrusts and thrusts of the Terpeniya Peninsula and mainly composed of Upper Cretaceous-Danian volcanosedimentary and volcanic rocks is a main morphostructural element of the Terpeniya Swell.